Impact of Guided Discovery Learning and Problem-Based Learning on Students’ Achievement and Locus of Control - Lazuardi Nugroho; Mathilda Susanti; Fariz Budi Arafat (IndoMath: Indonesia Mathematics Education, 2026)
Learning achievement is influenced by learning models and students’ locus of control. However, empirical evidence on the interaction between Guided Discovery Learning and Problem-Based Learning with locus of control is still limited, creating an urgent need for this study. Therefore, this research aims to investigate the effects of Guided Discovery Learning and Problem-Based Learning on students’ mathematics achievement by considering locus of control as a blocking variable. Using a quasi-experimental Randomized Complete Block Design, two groups of 32 seventh-grade students were assigned to GDL and PBL. Data from pretest–posttest instruments and an LoC questionnaire were analyzed using descriptive statistics and Two-Way ANOVA. Results showed that the learning model significantly affected achievement, while its interaction with LoC wasn’t significant, although I-LoC students performed better on average. These findings indicate that structured, supportive models like GDL and PBL can reduce LoC-related differences and emphasize the need for future mathematics instruction that promotes guided exploration and equitable learning environments.